2004
DOI: 10.1128/mcb.24.14.6278-6287.2004
|View full text |Cite
|
Sign up to set email alerts
|

Circadian and Light-Induced Transcription of Clock Gene Per1 Depends on Histone Acetylation and Deacetylation

Abstract: Circadian clock genes are regulated through a transcriptional-translational feedback loop. Alterations of the chromatin structure by histone acetyltransferases and histone deacetylases (HDACs) are commonly implicated in the regulation of gene transcription. However, little is known about the transcriptional regulation of mammalian clock genes by chromatin modification. Here, we show that the state of acetylated histones fluctuated in parallel with the rhythm of mouse Per1 (mPer1) or mPer2 expression in fibrobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
137
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(141 citation statements)
references
References 49 publications
3
137
0
Order By: Relevance
“…In this regard, we observed an enhanced upregulation of Per1 in mice that received the sodium butyrate as coadjuvant treatment of repeated morphine injections. Although we did not assess chromatin acetylation at this specific locus, it has been shown that both HDACi (Naruse et al, 2004) and cocaine (Renthal et al, 2009) can induce histone acetylation at the Per1 promoter and increase its transcription. Interestingly, the enhanced expression of Per1 in mice co-treated with sodium butyrate and morphine was associated to increased downregulation of Cry1 and upregulation of Rev-erba (Figure 5c).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, we observed an enhanced upregulation of Per1 in mice that received the sodium butyrate as coadjuvant treatment of repeated morphine injections. Although we did not assess chromatin acetylation at this specific locus, it has been shown that both HDACi (Naruse et al, 2004) and cocaine (Renthal et al, 2009) can induce histone acetylation at the Per1 promoter and increase its transcription. Interestingly, the enhanced expression of Per1 in mice co-treated with sodium butyrate and morphine was associated to increased downregulation of Cry1 and upregulation of Rev-erba (Figure 5c).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for involvement of chromatin modifications in light-inducible transcriptional activation is starting to accumulate (Crosio et al, 2000;Etchegaray et al, 2003;Naruse et al, 2004). Rhythmic acetylation of histone H3 at clock-regulated promoters has been correlated with the circadian activation of clock genes in mammals (Etchegaray et al, 2003;Hastings and Herzog, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…As histone deacetylase activity is constantly associated with the CLOCK⅐BMAL1 nuclear complex, the balance between acetylation and deacetylation of H3 on circadian promoters appears to be regulated by the rhythmic regulation of histone acetyltransferase activity, with deacetylation predominating during transcriptional repression. Other groups have also reported H3 acetylation rhythms at circadian promoters (17,18).…”
mentioning
confidence: 99%
“…As histone deacetylase activity is constantly associated with the CLOCK⅐BMAL1 nuclear complex, the balance between acetylation and deacetylation of H3 on circadian promoters appears to be regulated by the rhythmic regulation of histone acetyltransferase activity, with deacetylation predominating during transcriptional repression. Other groups have also reported H3 acetylation rhythms at circadian promoters (17,18).Our search for other chromatin remodeling activities involved in clockwork function has focused on mechanisms that would link deacetylase activity with other chromatin remodeling events involved in transcriptional inhibition by the mCRY proteins. One such link could be provided by the polycomb group (PcG) 5 proteins, which elicit chromatin-mediated transcriptional repression by both the deacetylation and methylation of H3 (19 -21).…”
mentioning
confidence: 99%
See 1 more Smart Citation